Improved performance in dye-sensitized solar cells by rationally tailoring anodic TiO2 nanotube length - Zhong, Peng (2013)
In this paper, highly ordered TiO2 nanotube arrays with the tube length in a very wide range between 10 and 100 μm are quickly fabricated on Ti sheets by using a modified electrochemical anodization process, and incorporated into dye-sensitized solar cells having the back-illuminated device architecture. Results indicate that the as-prepared TiO2 nanotube arrays have well-defined tube geometry, with a diameter around 100 nm at present conditions, and the nanotubes are in fact comprised by TiO2 nanoparticles other than single crystals. A maximum power conversion efficiency of 4.25% for the assembled DSSC can be achieved at an optimized nanotube length of 34 μm, which is consistent with the simulated results reported previously. By using the techniques of electrochemical impedance microscopy and open-circuit voltage decay, it has been further demonstrated that the vertically oriented TiO2 nanotube arrays work as direct electron transport paths, reduce the electron recombination, and thus enhance the electron collection efficiency, as compared to the mesoporous film based on TiO2 nanoparticles.